Of Human Bondage and the Question of Free Will - Mahinur Akşehir Uygur (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
Of Human Bondage (1915) by Somerset Maugham might be considered to be the story of a boy’s rite of passage, of a troubled love affair or to have a touch of Maugham’s own growth from boyhood to adulthood. However, the novel exceeds these simplistic approaches, touching upon the most intriguing questions of the human condition: the triggering principles of human actions and the question of free will. In this questioning, Maugham’s main philosophical inspiration is Baruch Spinoza (1632-1677) and he borrows the title of his book from Spinoza’s magnum opus, Ethics (1677) in which “Of Human Bondage” is the title of an episode. In his Ethics, Spinoza defines the concept of bondage as man’s inability to have full control over his actions and thoughts and he suggests that even though a human being has the knowledge of good and evil, certain faculties of human nature might lead to false knowledge or imperfection in his/her actions. The novel’s protagonist, Philip, who struggles with this bondage that surrounds him like an alien power that comes from within, as Maugham describes it, becomes the object of this discussion of human freedom or imprisonment carried out by Spinoza and other seventeenth and eighteenth century philosophers such as Francis Bacon, Thomas Hobbes and David Hume. Thus, the aim of this paper is to discuss the issue of the ‘inescapable’ bondage of man and the possibility of free will as embodied in Maugham’s Of Human Bondage.